Aggregating Human Judgment Probabilistic Predictions of Coronavirus Disease 2019 Transmission, Burden, and Preventive Measures. (25th July 2022) - Codi, Allison; Luk, Damon; Braun, David; Cambeiro, Juan; Besiroglu, Tamay; Chen, Eva; de Cesaris, Luis Enrique Urtubey; Bocchini, Paolo; McAndrew, Thomas
Abstract: Aggregated human judgment forecasts for coronavirus disease 2019 (COVID-19) targets of public health importance are accurate, often outperforming computational models. Our work shows that aggregated human judgment forecasts for infectious agents are timely, accurate, and adaptable, and can be used as a tool to aid public health decision making during outbreaks.